Multipotent mesenchymal stromal cells as treatment for poor graft function after allogeneic hematopoietic cell transplantation: A multicenter prospective analysis - Servais, Sophie; Baron, Frédéric; Lechanteur, Chantal; Seidel, Laurence; Baudoux, Etienne; Briquet, Alexandra; Selleslag, Dominik; Maertens, Johan; Poire, Xavier; Schroyens, Wilfried; Graux, Carlos; De Becker, Ann; et al. (Frontiers in Immunology, 2023)
Poor graft function (PGF) is a rare but serious complication of allogeneic hematopoietic cell transplantation (alloHCT). Due to their hematopoietic supporting properties and immune regulatory effects, multipotent mesenchymal stromal cells (MSC) could be considered a good candidate to help to restore bone marrow (BM) niches homeostasis and facilitate hematopoiesis after alloHCT. We prospectively assessed the efficacy and safety of ex-vivo expanded BM-derived MSC from third-party donor in a series of 30 patients with prolonged severe cytopenia and PGF after alloHCT. Within 90 days post-MSC infusion, 53% (95% CI, 35 – 71%) of patients improved at least one cytopenia (overall response, OR) and 37% (95% CI, 19 - 54%) achieved a complete hematological response (CR: absolute neutrophil count, ANC >0.5 x 109/L, Hb > 80g/L and platelet count > 20 x 109/L with transfusion independence). Corresponding response rates increased to 67% (95% CI, 50 - 84%) OR and 53% (95% CI, 35 - 71%) CR within 180 days after MSC infusion. A significant decrease in red blood cells and platelets transfusion requirement was observed after MSC (median of 30-days transfusion requirement of 0.5 and 0 from d90-120 post-MSC versus 5 and 6.5 before MSC, respectively, p ≤0.001). An increase in ANC was also noted by day +90 and +180, with 3/5 patients with severe neutropenia having recovered an ANC > 1 x 109/L within the 90-120 days after MSC infusion. Overall survival at 1 year post-MSC was 70% (95% CI, 55.4 – 88.5), with all but one of the patients who achieved CR being alive. A single infusion of third-party MSC appeared to be safe, with the exception of one deep vein thrombotic event possibly related to the intervention. In conclusion, a single i.v. infusion of BM-derived MSC from third party donor seemed to improve hematological function after alloHCT, although spontaneous amelioration cannot be excluded. Comparative studies are warranted to confirm these encouraging results. This multicenter trial was registered at www.clinicaltrials.gov (#NCT00603330).